A Facile Approach for 4D Microprinting of Multi‐Photoresponsive Actuators. Issue 1 (3rd October 2022) - Hsu, Li‐Yun; Mainik, Philipp; Münchinger, Alexander; Lindenthal, Sebastian; Spratte, Tobias; Welle, Alexander; Zaumseil, Jana; Selhuber‐Unkel, Christine; Wegener, Martin; Blasco, Eva
Abstract: For microscale 4D photoresponsive actuators, light is crucial in two ways. First, the underlying additive manufacturing techniques rely on photopolymerization processes triggered by the absorption of light. Second, the absorption of light serves as the actuation stimulus. The two absorptions can be conflicting. While the microstructure requires strong absorption at the actuation wavelength(s), this absorption should not interfere with that of the manufacturing process. Herein, a simple strategy is proposed to overcome these limitations and allow for the fabrication of multi‐photoresponsive 3D microstructures that can be actuated at different wavelengths of light. Two‐photon 3D laser printing is selected as the fabrication technique and liquid crystalline (LC) elastomers as the functional materials. In a first step, 3D microstructures are fabricated using an aligned LC ink formulation. Thereafter, up to five different dyes exhibiting absorptions that extend over the entire visible regime (400–700 nm) are successfully incorporated into the LC microstructures by an exchange process enabling a programmable actuation by irradiating with the suitable wavelength. Furthermore, by combining dyes exhibiting orthogonal absorptions, wavelength‐selective actuations are demonstrated. Abstract : A simple strategy allowing for the fabrication of multi‐phototoresponsive 4D microstructures using two‐photon laser writing that can be actuated at different wavelengths of light, is presented. In particular, three classes of dyes (azobenzenes, donor‐acceptor Stenhouse Adducts (DASAs), and anthraquinone) enabling actuation using blue, green or red light, respectively, are exploited.